Hubungan Sistem Pengendalian Internal dan Akuntabilitas Pengelolaan Keuangan pada Organisasi Perangkat Daerah Jawa Barat - Talakua, Victor Amanusa; Tetelepta, Johanis M. (ISAS, 2025)
This study aims to analyze the relationship between the internal control system and the accountability of financial management in Regional Apparatus Organizations of West Java Province. The research method uses a quantitative approach with a correlational design through the distribution of questionnaires to 98 respondents from 35 OPDs with budgets exceeding 50 billion rupiah. The data analysis technique uses descriptive statistics and simple linear regression with the assistance of SPSS version 26. The results of the study indicate that the implementation of the internal control system in West Java Province OPDs falls into the good category with an average score of 4.03, while the level of financial management accountability is also in the good category with an average score of 4.04.Hypothesis testing resulted in a calculated t-value of 14.762 with a significance of 0.000, proving that the internal control system has a positive and significant effect on financial management accountability. The coefficient of determination of 0.642 indicates that the internal control system is able to explain 64.2 percent of the variation in financial management accountability. This study concludes that improving the quality of the implementation of the internal control system will enhance the accountability of regional financial management, thus continuous strengthening of the five components of the internal control system is required, especially in the aspects of monitoring and risk assessment. Keywords: Internal Control System, Accountability, Regional Financial Management